Melatonin as a Chronobiotic and Cytoprotective Agent in Parkinson’s Disease - Pérez-Lloret, Santiago; Cardinali, Daniel P. (Frontiers in Pharmacology, 2021)
This review article discusses the special role that melatonin, an unusual phylogenetically conserved molecule present in all aerobic organisms, may have in prevention and treatment of Parkinson´s disease (PD). In human parkinsonism circulating melatonin levels are consistently disrupted and the potential therapeutic value of melatonin on sleep disorder in PD was suggested by a limited number of clinical trials, usually employing melatonin in the 2-5 mg/day range. Patients with PD showed decreased melatonin MT1 and MT2 receptor density in amygdala and substantia nigra, supporting the view that a disrupted melatonergic system could be involved in the altered sleep/wake cycle seen in PD. Approximately 3/4 of the dopaminergic cells in the substantia nigra pars compacta need to be lost to uncover motor symptomatology in PD. However, non-motor symptoms like hyposmia, depression or REM sleep behavior disorder (RBD) (characterized by the occurrence of vivid, intense and violent movements during REM sleep) precede the onset of PD for years and are index of worse prognosis Indeed, most of patients showing RBD (particularly men >50 years of age) will convert to an α-synucleinopathy within the 10 years of RBD. Daily administration of 3-12 mg of melatonin at bedtime is effective in the treatment of RBD and may halt neurodegeneration to PD. In animal model studies of PD melatonin was effective to curtail symptomatology. Allometric conversion of animal doses to projected cytoprotective melatonin doses for humans indicates a range in the 40-100 mg/day rarely employed clinically. Therefore, double-blind, placebo-controlled studies are urgently needed in this respect.